2000
DOI: 10.1016/s0148-2963(99)00011-9
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Affect as a Tool for Creating Value and Gaining Share of Customer

Abstract: Can the retail atmosphere be useful in developing long-lasting relationships many retailers inhabit, success driven retailers must find ways to maintain stability and grow in order to survive. each customer purchased one additional produce item, profitability would increase by more than 40%. Similarly, current customers who substituted two store-brand items for two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
391
1
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(430 citation statements)
references
References 29 publications
23
391
1
15
Order By: Relevance
“…Hedonic value derives from non-instrumental, experiential, emotional, and personally gratifying benefits (Hirschman and Holbrook, 1982) and may be associated with shopping, the use of media, and increased behavioral loyalty (Arnold and Reynolds, 2003;Babin and Attaway 2000;Babin et al, 1994;Jones, Reynolds, and Arnold, 2006;McQuail, Blumler, and Brown, 1972). Hedonic benefits may be relevant for loyalty programs through two dimensions: exploration and entertainment.…”
Section: Hedonic Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedonic value derives from non-instrumental, experiential, emotional, and personally gratifying benefits (Hirschman and Holbrook, 1982) and may be associated with shopping, the use of media, and increased behavioral loyalty (Arnold and Reynolds, 2003;Babin and Attaway 2000;Babin et al, 1994;Jones, Reynolds, and Arnold, 2006;McQuail, Blumler, and Brown, 1972). Hedonic benefits may be relevant for loyalty programs through two dimensions: exploration and entertainment.…”
Section: Hedonic Benefitsmentioning
confidence: 99%
“…To deepen knowledge about the effectiveness of loyalty programs, this research investigates perceived benefits and offers a scale to measure these benefits on the basis of various consumer experience (e.g., Babin and Attaway, 2000;Haley, 1968;Sheth et al, 1991;Tauber, 1972). A 16-item scale, with stable psychometric properties, captures these benefits.…”
Section: Implications For Relational Strategiesmentioning
confidence: 99%
“…The presence of positive stimulants encourage consumers to visit malls ( Mehrabian and Russell, 1974 ;Phillips and Sternthal, 1977 ;Bone and Ellen, 1999 ;Laroche et al , 2005 ) and the retail store environment has an effect on the consumer ' s moods, perceptions and attitudes ( Gardner, 1985 ;Michon et al , 2008 ) consequently infl uencing their purchase motivations and intentions. The store atmosphere affects the emotional and cognitive elements of consumers ( Stockil, 1972 ;Donovan and Rossiter, 1982 ;Bitner, 1992 ;Jackson and Konell, 1993 ;Babin and Attaway, 2000 ;Beyard et al , 2001 ;De Nisco and Napolitano, 2006 ) and infl uences the consumer ' s evaluation of products ( Baker et al , 1994 ). The design and ambience of malls add to their theatrical and pretentious character ( Belk and Bryce, 1993 ;El Sayed et al , 2004 ;Ooi and Sim, 2007 ).…”
Section: Mall Attributesmentioning
confidence: 99%
“…Several studies have suggested that excitement, feeling, emotion, interaction, and aesthetics should be included in perceived value (Guo & Yanan, 2010;Tsiros et al, 2004;Chaudhuri & Morris, 2001). Babin, Darden, & Griffin (1994) and Babin & Attaway, (2000) elucidated hedonic value and utilitarian value as two elements of perceived value. Hedonic values refer to more experiential orientation, emotional reaction on product attributes or usages, while utilitarian values come from functional benefits with the product.…”
Section: Perceived Valuementioning
confidence: 99%
“…Perceived value was modified from study of Babin & Attaway, (2000) and Babin et al (1994). A total of eight items were included in two facets, namely "hedonic value" and "utilitarian value".…”
Section: Questionnaire Design and Measurementmentioning
confidence: 99%